Is Additional Systematic Biopsy Necessary in All Initial Prostate Biopsy Patients With Abnormal MRI? - Cheng, Xueqing; Xu, Jinshun; Chen, Yuntian; Liu, Zhenhua; Sun, Guangxi; Yang, Ling; Yao, Jin; Zeng, Hao; Song, Bin (Frontiers in Oncology, 2021)
Purpose To determine whether additional systematic biopsy is necessary in all biopsy naïve patients with MRI visible lesions by taking PI-RADS score and prostate volume into consideration. Materials and Methods Patients who underwent combined systematic biopsy (SB) and cognitive MRI-targeted biopsy (TB) in our hospital between May 2018 and June 2020 were retrospectively reviewed. The detection rate of clinical significant prostate cancer (csPCa), biopsy grade group (GG) concordance, and disease upgrading rate on radical prostatectomy were compared between SB and TB and further stratified by PI-RADS v2.0 category and prostate volume. Results A total of 234 patients were analyzed in this study. TB alone detected more csPCa and less clinically insignificant prostate cancer (cisPCa) than SB alone in the whole cohort (57.3 vs 53%, P = 0.041; 3.8 vs 7.7%, P = 0.049 respectively). The additional SB indicated only a marginal increase of csPCa detection but a remarkable increase of cisPCa detection compared with targeted biopsy (59.4 vs 57.3%, P = 0.064; 3.8 vs 7.7%, P = 0.012). As stratified by PI-RADS category, the difference of csPCa detection rate between TB and SB was not significant either in PI-RADS 5 subgroup (83.8 vs 76.3%, P = 0.07) or in PI-RADS 3–4 subgroup (43.5 vs 40.9%, P = 1.0). Additional SB decreased the rate of disease upgrading on radical prostatectomy (RP) than TB alone in PI-RADS 3–4 subgroup (14.5 vs 25.5%, P = 0.031) other than PI-RADS 5 subgroup (6 vs 6%, P = 1.0). When stratified by prostate volume (PV), TB alone detected more csPCa than SB in small prostate (PV < 30 ml) group (81.0 vs 71.0%, P = 0.021) but not in large prostate (PV ≥ 30 ml) group (44.0 vs 42.7%, P = 0.754). The additional SB did not significantly decrease the rate of disease upgrading on RP than TB alone in either small or large prostate (6.4 vs 8.5%, P = 1.0; 13.8 vs 22.4%, P = 0.063). Conclusion The combination biopsy method was no superior than targeted biopsy alone in PI-RADS 5 or in small volume prostate subgroup.